Best Practice Injury Compensation Processes Following Intentional Vehicular Assaults and Other Large Scale Transport Incidents: A Delphi Review. (11th October 2023) - Varker, Tracey; McGregor, Kari; Pedder, David J.; Lethbridge, Ros; Grant, Genevieve; Knight, Holly; Jones, Kimberley A.; Jacobs, Jurriaan; O'Donnell, Meaghan
Abstract: Objective: Intentional vehicular assaults on civilians have become more frequent worldwide, with some resulting in mass casualties, injuries, and traumatized witnesses. Health care costs associated with these vehicular assaults usually fall to compensation agencies. There is, however, little guidance around how compensation agencies should respond to mental and physical injury claims arising from large-scale transport incidents. Methods: A Delphi review methodology was used to establish expert consensus recommendations on the major components of "no fault" injury claim processes for mental and physical injury. Results: Thirty-three international experts participated in a 3-round online survey to rate their agreement on key statements generated from the literature. Consensus was achieved for 45 of 60 (75%) statements, which were synthesized into 36 recommendations falling within the domains of (1) facilitating claims, (2) eligibility rules, (3) payments and benefits for clients, (4) claims management procedures, (5) making and explaining decisions, (6) support and information resources for clients, (7) managing scheme staff and organizational response, (8) clients with special circumstances, and (9) scheme values and integrity. Conclusions: The recommendations present an opportunity for agencies to review their existing claims management systems and procedures. They also provide the basis for the development of best practice guidelines, which may be adapted for application to compensation schemes in different contexts worldwide.